Cádiz y el liberalismo americano - Fazio, Mariano (Mercurio Peruano, 2013)
Attempts from a historical perspective to define the concept of liberalism and what elements contribute to its forming. Also, the essay outlines the peculiarities of liberalism in the Hispanic world in the context of accidental revolutions, without neglecting the importance of Scholastic thinking, until then reduced to the academic world but which flourishes in the time of Cadiz courts as support or alternative to the modern enlightened currents.
Keywords: liberalism, Enlightenment, Scholasticism, American Independence, European liberal thinking, Spanish liberalism.